Substrate metabolism during different exercise intensities in endurance-trained women - Romijn, J. A.; Coyle, E. F.; Sidossis, L. S.; Rosenblatt, J.; Wolfe, R. R. (Journal of Applied Physiology, 2000)
We have studied eight endurance-trained women at rest and during exercise at 25, 65, and 85% of maximal oxygen uptake. The rate of appearance (Ra) of free fatty acids (FFA) was determined by infusion of [2H2]palmitate, and fat oxidation rates were determined by indirect calorimetry. Glucose kinetics were assessed with [6,6-2H2]glucose. Glucose Ra increased in relation to exercise intensity. In contrast, whereas FFA Ra was significantly increased to the same extent in low- and moderate-intensity exercise, during high-intensity exercise, FFA Ra was reduced compared with the other exercise values. Carbohydrate oxidation increased progressively with exercise intensity, whereas the highest rate of fat oxidation was during exercise at 65% of maximal oxygen uptake. After correction for differences in lean body mass, there were no differences between these results and previously reported data in endurance-trained men studied under the same conditions, except for slight differences in glucose metabolism during low-intensity exercise (Romijn JA, Coyle EF, Sidossis LS, Gastaldelli A, Horowitz JF, Endert E, and Wolfe RR. Am J Physiol Endocrinol Metab 265: E380-E391, 1993). We conclude that the patterns of changes in substrate kinetics during moderate- and high-intensity exercise are similar in trained men and women.